Internalization of Manakarra Values ​​as a Basis for Character Education: Student Attitude in Focus - Yusran; Abdul Rahman R; Haedar; Feby Indayani; Sahril (Indonesian Journal of Educational Science (IJES), 2026)
The implementation of character education through the local wisdom of the Manakarra values carried out by students at the Faculty of Engineering, Tomakaka Mamuju University is an effort made to implement character education through the local wisdom of the 7 Manakarra values in shaping student behavior. The implementation of character education through manakarra methods using observation sheets and student interviews. The results of the study showed that the average percentage of manakarra mapia ateka' (faithful and pious) was 98.53%, maka' (intelligent and skilled) 100%, matona' (polite and modest) 98.53%, madoro tanni bassi' (honest and trustworthiness) 88.24%, mataratte' (behave in an orderly manner) 98.04%, matutu (be careful) 100%, mature base' base (sincerely serve) 90.20%. The implementation of character education through manakarra values has been implemented well in student activities on campus and outside the campus environment, with this application it can directly shape student behavior.